High frequency pacing of edge localized modes by injection of lithium granules in DIII-D H-mode discharges. (8th April 2016) - Bortolon, A.; Maingi, R.; Mansfield, D.K.; Nagy, A.; Roquemore, A.L.; Baylor, L.R.; Commaux, N.; Jackson, G.L.; Gilson, E.P.; Lunsford, R.; Parks, P.B.; Chrystal, C.; et al.
Abstract: A newly installed Lithium Granule Injector (LGI) was used to pace edge localized modes (ELM) in DIII-D. ELM pacing efficiency was studied injecting lithium granules of nominal diameter 0.3–0.9 mm, speed of 50–120 m s −1 and average injection rates up to 100 Hz for 0.9 mm granules and up to 700 Hz for 0.3 mm granules. The efficiency of ELM triggering was found to depend strongly on size of the injected granules, with triggering efficiency close to 100% obtained with 0.9 mm diameter granules, lower with smaller sizes, and weakly depending on granule velocity. Robust ELM pacing was demonstrated in ITER-like plasmas for the entire shot length, at ELM frequencies 3–5 times larger than the 'natural' ELM frequency observed in reference discharges. Within the range of ELM frequencies obtained, the peak ELM heat flux at the outer strike point was reduced with increasing pacing frequency. The peak heat flux reduction at the inner strike point appears to saturate at high pacing frequency. Lithium was found in the plasma core, with a concurrent reduction of metallic impurities and carbon. Overall, high frequency ELM pacing using the lithium granule injection appears to be compatible with both H-mode energy confinement and attractive H-mode pedestal characteristics, but further assessment is needed to determine whether the projected heat flux reduction required for ITER can be met.